The wedding date - Guillory, Jasmine (New York : Jove, 2018)
"A groomsman and his last-minute guest are about to discover if a fake date can go the distance in a fun and flirty debut novel. Agreeing to go to a wedding with a guy she gets stuck with in an elevator is something Alexa Monroe wouldn't normally do. But there's something about Drew Nichols that's too hard to resist. On the eve of his ex's wedding festivities, Drew is minus a plus one. Until a power outage strands him with the perfect candidate for a fake girlfriend. From the best man's toast to the bouquet toss, Alexa and Drew have more fun than they ever thought possible. But before they know it, Drew has to fly back to Los Angeles and his job as a pediatric surgeon, and Alexa heads home to Berkeley, where she's the mayor's chief of staff. Too bad they can't stop thinking about the other. They're just two high-powered professionals on a collision course toward the long distance dating disaster of the century--or closing the gap between what they think they need and what they truly want."--
Keywords: Dating (Social customs) -- Fiction; Mate selection -- Fiction; Romance fiction